PENDEKATAN GENERAL LINEAR MIXED MODEL PADA SMALL AREA ESTIMATION - Khairil A. Notodiputro; Anang Kurnia (FORUM STATISTIKA DAN KOMPUTASI, 2005)
Small area estimation is commonly used to describe smaller domain or sub-population. Small area estimation is an important measuring instrument to estimate parameter of smaller domain borrowing strength of population parameter estimate through statistical models with random influence. In this paper we showed the contribution of statistical methods in small area estimation using general linear mixed models.   Keywords :       small area estimation,  general linear mixed model